New opportunities for smart urban logistics - Results of a field study - Stephan Seeck; Maximilian Engelhardt (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: Sustainability and customer service of urban last mile logistics are lacking behind the expectations of today's society. This paper provides a holistic framework and empirical evidence of a field study ("Kiezbote") on evaluating smart urban logistics concepts with the purpose to increase customer service and improve ecological and economic sustainability of smart urban logistics concepts. Methodology: The smart urban logistics concept "Kiezbote" was tested in a 12-months field study in Berlin-Charlottenburg. We consolidated parcels in a micro-hub and delivered by cargo bike within 2h-time windows. Based on multiple quantitative and qualitative criteria, we developed a holistic framework to study feasibility, profitability, customer-centricity and effects on the environment. Findings: The findings indicate that our smart urban logistics concept outperforms the service-level of conventional parcel delivery by far. C02 emissions could be significantly reduced. The additional costs generated need to be covered by receiver, parcel logistics service provider and online-shops in order to enable economic implementation. Originality: This work closes the gap between many studies available in the literature dealing with smart urban logistics concepts and their missing practical implementation. This is one of the first completed field studies that provides an empirically grounded framework regarding environmental-friendly, economic viable AND customer-centric last mile delivery.
urn:nbn:de:gbv:830-882.0162212; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; City Logistics